GENDER CONTRIBUTION IN PRODUCTION OF HIGH VALUE CROPS: EMPIRICAL EVIDENCE FROM PAKISTAN - A. Ali; O. Erenstein; D. B. Rahut (Journal of Animal and Plant Sciences, 2014)
The present study estimated the impact of women’s participation in farming activities on labour demand, production of high value crops, household income and the number of cattle kept per household in Pakistan. The study was carried out in the rice wheat area of the Pakistani Punjab. The cross-sectional data set was collected from 106 female respondents both participating and not participating in farming activities. The data was analysed by employing the propensity score matching approach to account for potential bias which may arise due to systematic dissimilarities among participants and non-participants. The empirical results indicate that households having women’s participation were able to grow high value crops and have less demand for labour as compared to households having no women’s participation. The results indicate that participating households have a higher income and were able to keep more cattle. The women’s participation in farming activities in Pakistan needs to be encouraged to increase household income and reduce the poverty in rural areas.
Keywords: Women’s Participation; Labour Demand; Household Income; Propensity Score Matching; Punjab; Pakistan